Navigating digital platforms: a comparative study into Turkish political communication strategies on tiktok and twitch - Uyumaz, Canan; Islam, MD Nazmul (Department of Government Studies, Universitas Muhammadiyah Makassar, 2023)
This paper explores the use of new media platforms Twitch and TikTok by Turkish politicians leading up to the Presidential Elections of 2023. The paper focuses on the unique attributes of these platforms and establishes a comparison between the two by a coding scheme. This coding scheme has been constructed based on Cervi et al.’s (2023) methodological framework. It includes four themes: content, frequency, engagement, and interaction. These four themes will be examined through comparative analysis methodology. A selection of twenty TikTok videos for each sample and Twitch stream statistics will be analyzed by the numerical data, dates, and content pattern. To assess the political communication strategies that are applied by politicians, the paper will underline the possible importance of new media platforms in political campaigns. It should be noted that further research in this area is needed and there is also an emerging need to explore the evolving role of Twitch and TikTok in political campaigns.